Answer:
(f+g)(x) = 4x + 1
Step-by-step explanation:
(f+g)(x) = f(x) + g(x) = 3x -1 + x + 2
Combining the like terms:
3x + x - 1 + 2
= 4x + 1
Hence,
(f+g)(x) = 4x + 1
<em>Hope this helps and be sure to have a wonderful time ahead at Brainly! :D</em>
D because added up is 109 times 1.06 = 115.54 + the $5 shipping makes the answer $120.54
Answer: The answer should be -0.5
Step-by-step explanation:
Answer:
Step-by-step explanat
disculpa pero me voy a robar tus puntos no es nada personal
Answer:
these two apply:
10x + 12 = 38 and
10x = 26
Step-by-step explanation:
7x+6+3x+6 = 38
10x + 12 = 38
10x = 26
x = 2.6